2023
DOI: 10.3390/cancers15123096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shape Irregularity in Medial Sphenoid Wing Meningiomas on Postoperative Cranial Nerve Functioning, Proliferation, and Progression-Free Survival

Johannes Wach,
Johannes Naegeli,
Martin Vychopen
et al.

Abstract: Medial sphenoid wing meningiomas (MSWM) are surgically challenging skull base tumors. Irregular tumor shapes are thought to be linked to histopathology. The present study aims to investigate the impact of tumor shape on postoperative functioning, progression-free survival, and neuropathology. This monocentric study included 74 patients who underwent surgery for primary sporadic MSWM (WHO grades 1 and 2) between 2010 and 2021. Furthermore, a systematic review of the literature regarding meningioma shape and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In an analysis involving 303 patients who underwent surgical removal of non-skull or skull base meningiomas classified as WHO grades 1–3, it was revealed that decreased sphericity significantly predicted both local meningioma regrowth and survival. In a previous institutional series, we could also identify sphericity as a surrogate parameter regarding postoperative cranial nerve functioning after surgery for medial sphenoid wing meningioma ( 15 ). Furthermore, an irregular shape was found to be significantly associated with increased proliferative activity, as reflected by the MIB-1 index, in medial sphenoid wing meningiomas ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an analysis involving 303 patients who underwent surgical removal of non-skull or skull base meningiomas classified as WHO grades 1–3, it was revealed that decreased sphericity significantly predicted both local meningioma regrowth and survival. In a previous institutional series, we could also identify sphericity as a surrogate parameter regarding postoperative cranial nerve functioning after surgery for medial sphenoid wing meningioma ( 15 ). Furthermore, an irregular shape was found to be significantly associated with increased proliferative activity, as reflected by the MIB-1 index, in medial sphenoid wing meningiomas ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous institutional series, we could also identify sphericity as a surrogate parameter regarding postoperative cranial nerve functioning after surgery for medial sphenoid wing meningioma ( 15 ). Furthermore, an irregular shape was found to be significantly associated with increased proliferative activity, as reflected by the MIB-1 index, in medial sphenoid wing meningiomas ( 15 ). However, in the present series, we could not observe a correlation between the shape of primary dorsal SMs and the number of mitotic figures or the MIB-1 index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analysis was conducted on the specimen, using the Molecular Immunology Borstel-I (MIB-I, DAKO, Glostrup, Denmark) antibody for Ki67 antigen detection. The MIB-I index was determined using the average method as previously described ( 26 ).…”
Section: Methodsmentioning
confidence: 99%